How can we elicit more complex thinking in Year 7 students for understanding and resolving life-issues? - Smith, Thomas Richard (International journal of Christianity & education, 2017)
This article explores the cognitive processes by which Year 7 students (aged 11 to 13 years) use personal viewpoints to interpret and resolve life-issues. A Christian school located in the North West of Sydney wanted to find out if the proportionally higher occurrence of discipline issues in newly enrolled Year 7 students could be explained by those students having a more diverse range of personal viewpoints than Year 7 students who had been enrolled for a longer time. To address this question, we conducted a survey of Year 7 students at the school in early 2015. The survey consisted of five open-ended questions related to a hypothetical school bullying situation. The students' answers were coded according to the various types of personal viewpoints they used to form an interpretation of the scenario event and to resolve the issue. The students' responses reflected 18 personal viewpoints across the five questions. Their answers varied in their use of complex personal viewpoints - that is, answers consisting of two or more simple personal viewpoints. A pattern was discerned from the varying proportions of complex viewpoints each question elicited, some questions drawing a high proportion of complex viewpoints. The differing proportions of complex personal viewpoints used in answering each of the five questions suggested that a higher proportion of complex personal viewpoints indicated the occurrence of enhanced complex thinking. A further finding was that students used a higher proportion of complex personal viewpoints when answering questions that challenged them to take a third-person perspective on the protagonists in the narrative.